2009
DOI: 10.5551/jat.1156
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ApolipoproteinCII Concentrations on HDL Subclass Distribution

et al.

Abstract: Aim:To demonstrate the interrelationship between plasma apolipoprotein(apo)C concentrations and the pattern of high-density lipoprotein (HDL) subclass distribution. Methods: ApolipoproteinA-contents of plasma HDL subclasses were quantified by 2-dimensional gel electrophoresis associated with immunodetection in 504 Chinese subjects. Results: Compared with subjects in the lowest tertile of the apoC group, the contents of pre 1-HDL, HDL3b, and HDL3a were significantly higher than HDL2a and HDL2b in subjects in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
0
7
0
6
Order By: Relevance
“…In addition, to divide apoC-II into tertiles among the whole population and the study showed compared to the lowest tertile of apoC-II, the subjects with the highest tertile of apoC-II represent a typical HTG lipids profile [ 17 , 18 ]. The higher TG concentrations were associated with the levels of apoC-II and apoC-III increased, and an increasing in apoC-II more prominent than in apoC-III which conduces to the apoC-III/C-II ratio declined.…”
Section: The Effect Of Plasma Lipids Combined With Apolipoproteins Onmentioning
confidence: 99%
“…In addition, to divide apoC-II into tertiles among the whole population and the study showed compared to the lowest tertile of apoC-II, the subjects with the highest tertile of apoC-II represent a typical HTG lipids profile [ 17 , 18 ]. The higher TG concentrations were associated with the levels of apoC-II and apoC-III increased, and an increasing in apoC-II more prominent than in apoC-III which conduces to the apoC-III/C-II ratio declined.…”
Section: The Effect Of Plasma Lipids Combined With Apolipoproteins Onmentioning
confidence: 99%
“…215 In APOCII-deficient patients, the mature HDL subfractions have been reported to be reduced or lacking. 216,217 Apolipoprotein AV ApoA-V can be considered as a modulator of LPL activity. APOAV (11q23) is expressed in the liver and the protein is secreted into plasma, where it associates with VLDL, chylomicrons, and HDL.…”
Section: Determinants Of Lpl Activitymentioning
confidence: 99%
“…CHD patients have significantly lower serum apoC-II concentrations than normal subjects [35]. Although excess apoC-II has been associated with a smaller HDL particle size [36], the increase in the relative abundance of HDL-bound apoC-II in the participants in whom HDL-C concentrations were increased with the MedDiet may reflect an overall enhanced capacity of lipolysis of triglyceride-rich lipoproteins. Further studies are needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%